2014
DOI: 10.1145/2740070.2626328
|View full text |Cite
|
Sign up to set email alerts
|

FireFly

Abstract: Conventional static datacenter (DC) network designs offer extreme cost vs. performance tradeoffs---simple leaf-spine networks are cost-effective but oversubscribed, while "fat tree"-like solutions offer good worst-case performance but are expensive. Recent results make a promising case for augmenting an oversubscribed network with reconfigurable inter-rack wireless or optical links. Inspired by the promise of reconfigurability, this paper presents FireFly, an inter-rack network solution that pushes DC network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…In our previous work [7], a simple prototype FSO terminal with the goal of achieving 360 • -steerable communication for HPC use has been developed. It keeps a 1.6-mm positioning error at a 30-m distance, which is well within the 6-mm tolerance of an FSO link [14]. Furthermore, an experiment using Arimoto's devices [17] has confirmed that the optical power loss over a 30-m indoor FSO link is well within SFP/XFP/QSFP standards.…”
Section: Behaviorsupporting
confidence: 60%
See 1 more Smart Citation
“…In our previous work [7], a simple prototype FSO terminal with the goal of achieving 360 • -steerable communication for HPC use has been developed. It keeps a 1.6-mm positioning error at a 30-m distance, which is well within the 6-mm tolerance of an FSO link [14]. Furthermore, an experiment using Arimoto's devices [17] has confirmed that the optical power loss over a 30-m indoor FSO link is well within SFP/XFP/QSFP standards.…”
Section: Behaviorsupporting
confidence: 60%
“…Free Space Optics (FSO) is utilized for high-bandwidth high-frequency wireless communication (e.g., several hundreds THz band for carrier signal) [7], [14]. FSO communication systems have been designed and deployed for home networks, indoor networks, inter-building links, links between two mobile vehicles, and long-distance data transfers such as high-bandwidth satellite communication.…”
Section: Free Space Optics (Fso)mentioning
confidence: 99%
“…In [8], Hamedazimi et al suggested a dynamic reconfigurable design for data center networks. In this work, the authors proposed a wireless network in which Free Space Optic (FSO) links are installed for inter-rack communication.…”
Section: Related Workmentioning
confidence: 99%
“…If the network interconnection could "shape-shift" in such fashion, this could considerably simplify the complicated workload placement problem. Several reconfigurable optical DCNs architectures such as ProjecToR, FireFly and OSA supporting flexible bandwidth and capacity allocation have been proposed [19,20,21]. However, the ProjecToR and FireFly based on the wireless connections have to guarantee the line-of-sight between the TRX pairs.…”
Section: Introductionmentioning
confidence: 99%